Optimization of Environmental Conditions for Microbial Stabilization of Uranium Tailings, and the Microbial Community Response - Lv, Ying; Tang, Chuiyun; Liu, Xingyu; Zhang, Mingjiang; Chen, Bowei; Hu, Xuewu; Chen, Susu; Zhu, Xuezhe (Frontiers in Microbiology, 2021)
Soil pollution caused by uranium and its decay products is a global environmental problem. It is of great significance to use reasonable technologies to remediate uranium-contaminated soil. In this study, the effects of pH, temperature and inoculation volume on stabilization efficiency and microbial community structure of uranium tailings were investigated by single factor batch experiment in the remediation process by mixed sulfate-reducing bacteria (SRB) and phosphate-solubilizing bacteria (PSB, Pantoea sp. grinm-12). The results showed that the optimal parameters of microbial stabilization by mixed SRB-PSB were pH of 5.0, temperature of 25ºC and inoculation volume of 10%. Under the optimized conditions, the uranium in uranium tailings presented a tendency to transform from acid soluble state to residue state. In addition, the introduction of exogenous SRB-PSB can significantly increase the richness and diversity of endogenous microorganisms, effectively maintain the reduction environment for microbial stabilization system, and promote the growth of functional microorganisms, such as sulfate-reducing bacteria (Desulfosporosinu and Desulfovibrio) and iron-reducing bacteria (Geobacter and Sedimentibacter). Finally, PCoA and CCA analysis showed that temperature and inoculation volume had significant effects on microbial community structure, and the influence order of the three environmental factors followed: inoculation volume > temperature > pH. The outcomes of this study provide theoretical support for the control of uranium in uranium-contaminated sites and have important significance for uranium mineralization and migration in environmental biogeochemistry.